2013
DOI: 10.1002/jcph.13
|View full text |Cite
|
Sign up to set email alerts
|

Do Children Have the Same Vulnerability to Metabolic Drug–Drug Interactions as Adults? A Critical Analysis of the Literature

Abstract: Many drug-drug interactions (DDIs) in the pediatric population are managed based on data generated in adults. However, due to developmental changes in elimination pathways from birth to adolesence, and variable weight-adjusted dose of interacting drugs, the assumption of DDIs being similar in adults and pediatrics might not be correct. This study compares the magnitude of reported DDIs in pediatric and adult populations. A systematic literature review was undertaken to identify reports of DDIs in pediatric sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 31 publications
0
54
0
1
Order By: Relevance
“…The practitioner should consult various sources (a pharmacist, textbooks, online services, or handheld databases) for specific information on drug interactions. [315][316][317][318][319] The US Food and Drug Administration issued a warning in February 2013 regarding the use of codeine for postoperative pain management in children undergoing tonsillectomy, particularly those with OSA. The safety issue is that some children have duplicated cytochromes that allow greater than expected conversion of the prodrug codeine to morphine, thus resulting in potential overdose; codeine should be avoided for postprocedure analgesia.…”
Section: Documentation At the Time Of Sedationmentioning
confidence: 99%
“…The practitioner should consult various sources (a pharmacist, textbooks, online services, or handheld databases) for specific information on drug interactions. [315][316][317][318][319] The US Food and Drug Administration issued a warning in February 2013 regarding the use of codeine for postoperative pain management in children undergoing tonsillectomy, particularly those with OSA. The safety issue is that some children have duplicated cytochromes that allow greater than expected conversion of the prodrug codeine to morphine, thus resulting in potential overdose; codeine should be avoided for postprocedure analgesia.…”
Section: Documentation At the Time Of Sedationmentioning
confidence: 99%
“…Despite this increase, many workers still retire before the official retirement age of 65 years. Currently, the general population is aging because of decreasing birth rates [2] and increasing longevity [3]. Moreover, the baby boom generation has started to leave work.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported that the combination of LTG with VPA achieves a significantly better response than combinations of LTG with other AEDs, and this differential response is associated with a strong pharmacodynamic interaction that leads to anticonvulsant synergy [16,24]. In routine clinical practice, most measured samples (58.7%) were from patients receiving combination therapy with LTG and VPA.…”
Section: Discussionmentioning
confidence: 99%
“…LTG þ multiple inducers or LTG þ VPA þ one or more inducers). Salem et al [16] reviewed 145 reports of drug interactions and suggested that interactions were more severe in children under 2 years old than in adults. Unfortunately, there have only been a few investigations of the pharmacokinetics of LTG in pediatric patients [1,3,6,7,10,14] and its plasma concentration profile in children less than 3 years old is unknown.…”
Section: Introductionmentioning
confidence: 99%